Current systematic reviews of the burden of covid-19 pandemic in children and adolescents - Doina Anca Plesca; Cristina Radulescu; Alexandra Vilaia; Plesca Vlad Stefan; Anca Cristina Dragnescu (Amaltea Medical Publishing House, 2022)
The coronavirus disease 2019 (COVID-19) is profoundly affecting life of the children and adolescents around the globe. The authors present a synthesis of the characteristics of SARS CoV-2 infection in the pediatric population. The role played by children in the transmission of infection as well as the changes related to the clinical picture and the severity of symptoms that changed during the 5 pandemic waves. Another objectives of this review was to describe the diverse facets of the burden of COVID-19 in children and adolescents. The authors presented the direct effects of hospitalization during the acute phase of the disease, multisystem inflammatory syndrome in children, long COVID and the sequelae after infection with the new coronavirus. In addition, the indirect effects of social isolation and interruption in education are discussed. Isolation, contact restrictions and economic shutdown impose a complete change to the psychosocial environment in affected countries. Mental health problems among children and adolescents are increasingly reported amidst the coronavirus disease (COVID-19) pandemic. Anxiety, lack of peer contact and reduced opportunities for stress regulation are main concerns. Another main threat is an increased risk for parental mental illness, domestic violence and child maltreatment. The burden of the COVID-19 pandemic manifested in various ways: there was an increase in poverty, a major crisis arose in education, and new threats concerning children's health and even survival emerged.